Test-retest reliability of the isometric contraction test (IC test) of the masticatory muscles in subjects with and without temporomandibular muscle disorders - Marcos IGLESIAS-PEÓN; Juan MESA-JIMÉNEZ; César FERNÁNDEZ-; Nuria GARCÍA IGLESIAS; Carmen María IGLESIAS PEÓN; Daiana Priscila RODRIGUES-; Francisco ALBURQUERQUE-SENDÍN (University of São Paulo, 2023)
Abstract Recently, the DC/TMD has become an essential tool for the diagnosis of temporomandibular disorders (TMD). However, as they fail to include functional activities, new assessment proposals have emerged, such as the isometric contraction test (IC test) of the masticatory muscles, which uses muscle contractions to identify muscular TMD. Objective This study aimed to determine the test-retest reliability of the IC test. Methods A total of 64 participants (40 women and 24 men) completed the IC test administered by two different physical therapists on two non-consecutive days. Cohen's kappa (k), PABAK, and percent agreement (PA) between days were estimated. Results The IC test showed good to excellent test-retest reliability values (k>0.77; PABAK>0.90), both globally and individually for the muscles evaluated, and PA>90%, therefore above the thresholds for clinical applicability. However, the global assessment of myofascial pain and the evaluation of the medial pterygoid muscle showed slightly lower reliability values. Conclusion The IC test is reliable for the assessment of subjects with muscular TMD, both in terms of the global assessment and the evaluation of each muscle, which supports its clinical applicability. Care should be taken when assessing myofascial pain globally and when evaluating the medial pterygoid in all types of pain.